The creation of a rite: a semiotic analysis of a union protest through the twitter social network during the state of pandemic - Yalán Dongo, Eduardo (2021)
This article aims to analyze protest practices as a ritual registered through the Twitter platform during the state of pandemic. To that end, from a qualitative approach using social semiotics analysis techniques, this research takes as corpus or empirical reality of analysis tweets with audiovisual content posted by the Sanitation Workers’ Union (SITOBUR) from June to September 2020, the time frame during the pandemic in which labor protests were exacerbated. Since the interest is not the becoming protest from the rite but the becoming rite from the protest, the semiotics of the ritual is considered a vital concept for the production of meaning in protest practices, not only from the perspective of its aesthetic performance but also as an element cooperating with the directionality of such practice. The results of the social semiotics analysis lead us to recognize lurking as a significant form of rite which is present in the protests during their spatial, temporal, actantial and practical development.